From New to Indispensable: How the 2004 Enlargement Reshaped the EU’s Transformative Powers - Matej Navrátil; Marko Lovec (Politics and Governance, 2024)
This editorial introduces a thematic issue that examines the consequences of the accession of the Central and East European countries to the EU 20 years onward. The socioeconomic transformation of these countries in the pre-accession period was considered a remarkable success, that was attributed to the EU’s conditionality policy. However, in the post-accession period, when these countries gained full membership rights and began playing a more active political role, they started deviating from some EU norms and rules, against a backdrop of EU crises. This shift has been, notably, reflected in concerns about democratic backsliding and rule of law violations. Nonetheless, the contributions in this issue also underscore that these countries have internalized (both top-down and bottom-up) EU norms and rules to a much greater extent than the focus on conditionality would suggest. Moreover, since Russia invaded Ukraine, Central and East European countries have become entrepreneurs of EU policy and bolstered its transformative power. These findings indicate a need to focus not only on the fundamental shortcomings in these countries—as the attention conferred to the (lack of post-accession) conditionality suggests—but also to consider other factors, such as the quality of the EU’s governance and political system, policy learning, geopolitics, and member states’ domestic politics.